2014
DOI: 10.1097/ncq.0b013e3182a71d43
|View full text |Cite
|
Sign up to set email alerts
|

Development and Pilot Testing of a Patient-Participatory Pressure Ulcer Prevention Care Bundle

Abstract: This study developed and piloted a patient-centered pressure ulcer prevention care bundle for adult hospitalized patients to promote patient participation in prevention. The care bundle had 3 core messages: (1) keep moving, (2) care for your skin, and (3) ensure a good diet. A brief video, combined brochure/checklist, and poster were developed as training resources. Patient evaluation identified benefits of the care bundle; however, the combined checklist/brochure was rarely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 15 publications
2
36
0
1
Order By: Relevance
“…This results is incongruence with Sathiya et al [17] who stated that regarding the prevention from developing pressure ulcers, nearly three quarters of participants had adequate knowledge about frequent position change and minority of them had adequate knowledge that utilize of pillow/ rolled blanket/air mattress to alleviate continue pressure from developing bedsore. Similar finding was reported by Mohamed and Weheida [18] & and Gillespie et al [19] who stated that majority of caregivers and patients had insufficient knowledge related to basic principles of prevention including devices valuable in pressure ulcer prevention, pressure reducing mattresses and the study concluded that families and caregivers of immobilized patients have unsatisfactory knowledge of pressure ulcer prevention.…”
Section: Discussionsupporting
confidence: 75%
“…This results is incongruence with Sathiya et al [17] who stated that regarding the prevention from developing pressure ulcers, nearly three quarters of participants had adequate knowledge about frequent position change and minority of them had adequate knowledge that utilize of pillow/ rolled blanket/air mattress to alleviate continue pressure from developing bedsore. Similar finding was reported by Mohamed and Weheida [18] & and Gillespie et al [19] who stated that majority of caregivers and patients had insufficient knowledge related to basic principles of prevention including devices valuable in pressure ulcer prevention, pressure reducing mattresses and the study concluded that families and caregivers of immobilized patients have unsatisfactory knowledge of pressure ulcer prevention.…”
Section: Discussionsupporting
confidence: 75%
“…The positive response of nurses to a PUPCB promoting patient participation in PUP care may be partly due to the PUPCB being developed in collaboration with end users; that is, the views of patients and nurses were sought in a pilot study and their feedback was incorporated into the final design of the intervention [6, 20]. This is in line with an integrated knowledge translation approach, which is used to develop interventions that are likely to be relevant, acceptable and usable to end-users [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses have a primary role in PUP; however patients may also contribute through active participation in PUP care [5, 6]. Patient participation in care has been shown to result in improved patient safety [7] and satisfaction with care [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus the intervention is patient-centred and reflects partnership between patients and nurses in the delivery of care. The intervention was previously developed and piloted in an acute tertiary hospital setting Gillespie, 2014, Gillespie et al, 2014). Awareness of the INTACT trial will be raised through a range of strategies such as hospital newsletters, e-mails and forums.…”
Section: Interventionmentioning
confidence: 99%
“…Consequently, an innovative PIP strategy was developed Gillespie, 2014, Gillespie et al, 2014) that is intended to optimise efficacy and sustainability, namely a care bundle that incorporates patient participation in care, easy access to PIP information and nursing staff engagement. This paper reports the protocol currently being used to test this care bundle, namely the INTACT trial (INTroducing A Care bundle To prevent pressure injury in at-risk patients).…”
Section: Introductionmentioning
confidence: 99%